2008
DOI: 10.1016/j.marmicro.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical investigation of gametogenic calcite addition in the planktonic foraminifera Orbulina universa

Abstract: Several species of planktonic foraminifera precipitate a final layer of calcite onto the shell surface immediately prior to gamete release at the end of the foraminifera life cycle. Here, we present the results of carbon-13, oxygen-18 and thermal labeling experiments conducted under high (HL) and low light (LL) regimes that vary symbiont photosynthetic activity. Mean experimental group data show that gametogenic (gam) calcite contributes between 4-17% and 14-20% to final shell mass for high and low light exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…However, it was also shown that the amount of gametogenic calcite was constant (ca. 4 μg) independent of size (Hamilton et al, 2008). The fact that the foraminifera we analysed often still had their spines or remains thereof indicate that gametonenetic calcite was not present.…”
Section: Foraminiferal Apparent Calcification Depthmentioning
confidence: 86%
“…However, it was also shown that the amount of gametogenic calcite was constant (ca. 4 μg) independent of size (Hamilton et al, 2008). The fact that the foraminifera we analysed often still had their spines or remains thereof indicate that gametonenetic calcite was not present.…”
Section: Foraminiferal Apparent Calcification Depthmentioning
confidence: 86%
“…The sphere is the final chamber addition phase of this species. During gametogenesis, O. universa sheds its spines and adds a thin veneer of calcite that contributes~4-20% to the final shell calcite prior to the release of its gametes (Hamilton et al, 2008). Small and large pores on the final chamber serve as pathways for gas exchange and food and symbiont movement into and out of the cell protoplasm, respectively (Bé et al, 1980;Spero, 1987Spero, , 1988.…”
Section: Orbulina Universa: Life Cycle Habitat Preferences and Morphmentioning
confidence: 99%
“…Based on oxygen isotopic compositions of pooled sediment trap shells and depth-stratified plankton tow samples, Deuser et al (1981) concluded that the thinner of the two morphotypes calcified at depths between 25 and 50 m, while the thicker morphotype calcified in deeper water. The thickness variations between the two morphotypes were ultimately attributed to the presence or absence of gametogenic calcite, though later studies suggest that the O. universa morphotypes from these studies may represent different cryptic species (Hamilton et al, 2008). Deuser (1987) also report that the differences between the oxygen isotopic compositions of the thick and thin varieties of O. universa is minimal during periods when the mixed layer is deep and increases rapidly as a more stratified water column is established.…”
mentioning
confidence: 98%
“…Therefore, there is evidence to reject the hypothesis of a daily pH change in the microenvironment being responsible for Mg-and Sr-banding within the chamber walls. Sadekov et al (2005) showed that the high-Mg/Ca bands are found in all but the last chamber; an observation that can be explained by gametogenesis, where a different calcification mechanism is responsible only for the formation of this chamber (Hamilton et al, 2008). This causes the high-Mg/low-Mg band ratio to vary between chambers resulting in slightly different Mg/Ca values among them: the final chamber has a relatively low Mg/Ca value, whereas previous chambers have higher Mg contents (Fig.…”
Section: Ontogenetic Variation Of Sr/camentioning
confidence: 99%
“…Recently, Hamilton et al (2008) showed that the planktonic foraminifer Orbulina universa, adds a constant amount of calcite, of about 4 lg, to their tests during gametogenesis. When foraminifera add this so-called GAM-calcite deeper in the water column we expect it to be relatively depleted in Mg, because of the lower temperatures.…”
Section: A Size-normalized Mg/ca-based Temperature Calibrationmentioning
confidence: 99%